Outbreak of Foodborne Botulism Associated With Prepackaged Pouches of Liquid Herbal Tea. (9th February 2019) - Kim, Moon; Zahn, Matt; Reporter, Roshan; Askar, Ziad; Green, Nicole; Needham, Michael; Rosen, Hilary; Kimura, Akiko; Terashita, Dawn
Abstract: Background: In 2017, local public health authorities in California received reports of 2 elderly patients with suspected botulism who knew each other socially. A multijurisdictional investigation was conducted to determine the source. Methods: Investigators reviewed medical records, interviewed family to establish food and drink histories, and inspected a facility that produced liquid herbal tea. Clinical specimens and product were tested for botulinum neurotoxin (BoNT). Results: A total of 2 confirmed botulism cases were identified with BoNT type A; both were hospitalized, 1 died. Botulism was not suspected until several days after hospital admission. Case-patients ingested single-serving prepackaged liquid herbal tea. Inspection of the tea production facility identified conditions conducive to product contamination with C botulinum and toxin production. Samples of tea tested negative for botulinum toxin. Local and state public health authorities issued alerts and the facility recalled the liquid herbal tea. Conclusions: Liquid herbal tea prepackaged in sealed pouches was the likely source of this type A botulism outbreak because the 2 cases were linked socially and shared no other foods. This type of product has not previously been described in the foodborne botulism literature. In the absence of known risk factors for botulism at the time of presentation, suspicion based on clinically compatible findings is critical so that and treatment with botulinum antitoxin is not delayed. A coordinated response by public health authorities is necessary in identifying a potential food source, inspecting facilities producing the product, alerting medical providers and the public, and preventing further illness.